(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Periodontitis is a multifactorial disease that mainly affects the supporting tissues of the teeth. Treatment options like mechanical debridement and administration of antimicrobial drugs have been applied in the management of periodontal diseases. The local drug delivery (LDD) system is one of the potentially effectivemethod in the management of periodontal diseases. It is not suitable for use as a monotherapy since it performs better clinically when used in conjunction with scaling and root planing